A Modified Progressive Supranuclear Palsy Rating Scale. Issue 5 (29th January 2021) - Grötsch, Marie‐Therese; Respondek, Gesine; Colosimo, Carlo; Compta, Yaroslau; Corvol, Jean Christophe; Ferreira, Joaquim; Huber, Meret Koroni; Klietz, Martin; Krey, Lea F.M.; Levin, Johannes; Jecmenica‐Lukic, Milica; Macías‐García, Daniel; et al.
ABSTRACT: Background: The Progressive Supranuclear Palsy Rating Scale is a prospectively validated physician‐rated measure of disease severity for progressive supranuclear palsy. We hypothesized that, according to experts' opinion, individual scores of items would differ in relevance for patients' quality of life, functionality in daily living, and mortality. Thus, changes in the score may not equate to clinically meaningful changes in the patient's status. Objective: The aim of this work was to establish a condensed modified version of the scale focusing on meaningful disease milestones. Methods: Sixteen movement disorders experts evaluated each scale item for its capacity to capture disease milestones (0 = no, 1 = moderate, 2 = severe milestone). Items not capturing severe milestones were eliminated. Remaining items were recalibrated in proportion to milestone severity by collapsing across response categories that yielded identical milestone severity grades. Items with low sensitivity to change were eliminated, based on power calculations using longitudinal 12‐month follow‐up data from 86 patients with possible or probable progressive supranuclear palsy. Results: The modified scale retained 14 items (yielding 0–2 points each). The items were rated as functionally relevant to disease milestones with comparable severity. The modified scale was sensitive to change over 6 and 12 months and of similar power for clinical trials of disease‐modifying therapy as the original scale (achieving 80% power for two‐sample t test to detect a 50% slowing with n = 41 and 25% slowing with n = 159 at 12 months). Conclusions: The modified Progressive Supranuclear Palsy Rating Scale may serve as a clinimetrically sound scale to monitor disease progression in clinical trials and routine. © 2021 International Parkinson and Movement Disorder Society